2021
DOI: 10.1136/bmjgast-2021-000662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disease duration on the association between serum albumin and mucosal healing in patients with ulcerative colitis

Abstract: ObjectiveSerum albumin is used as a marker of acute inflammation. Several studies have addressed the association between serum albumin and clinical outcome in patients with ulcerative colitis (UC). While mucosal healing (MH) has been indicated as the therapeutic goal for UC, the association between serum albumin and MH remains unclear. We evaluated this issue in patients with UC overall and explored whether duration of UC affected this association.DesignThis cross-sectional study recruited consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In patients with UC, on the other hand, the immunochemical fecal occult blood test as a biomarker for MH is more accurate in patients with disease duration < 4 years [ 25 ]. Similarly, serum albumin was found to be a useful marker for MH in patients with shorter UC duration but not in those with longer UC duration [ 26 ]. In the present study, CAR was associated with disease activity only in UC patients with longer disease duration but not in those with shorter disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with UC, on the other hand, the immunochemical fecal occult blood test as a biomarker for MH is more accurate in patients with disease duration < 4 years [ 25 ]. Similarly, serum albumin was found to be a useful marker for MH in patients with shorter UC duration but not in those with longer UC duration [ 26 ]. In the present study, CAR was associated with disease activity only in UC patients with longer disease duration but not in those with shorter disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our observations of increasing levels of CRP and decreasing albumin with inflammatory burden, as expressed in high PUCAI scores. While CRP seems to reflect active mucosal inflammation in the colon [ 30 ], serum albumin positively correlates with mucosal healing [ 33 ]. Thus, hypoalbuminemia enables clinical course prediction at diagnosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report a significant inverse relationship between low serum albumin and risk of colectomy[ 72 ]. Conversely, studies in UC patients have shown that mucosal healing is positively associated with high (> 4.4 mg/dL) serum albumin[ 73 ].…”
Section: Putting It All Togethermentioning
confidence: 99%